Revisiting Macrophage Plasticity: From M1/M2 Polarization to Immune Modulation in Cancer Therapy - Rasheka Mathur; Yasmin Bano; Anshika Gupta; Sakshi Chauhan; Prince Sharma; Dhananjay Dhar Dwivedi; Rohini Saha; Pramod Kumar; Dinesh Kumar Singhal (Current Molecular Medicine, 2026)
Macrophages play a key role in organizing the immune system's response to different types of infections. Their remarkable plasticity enables them to develop and polarize into M1 (tumor-suppressing) and M2 (tumor-promoting) macrophages, in addition to Tumor-Associated Macrophages (TAMs). This thorough review examines how distinct signaling inducers affect macrophage polarization and behavior across various cancer types, including breast, lung, hepatocellular, prostate, and cervical cancers. In colorectal cancer, however, they have the opposite effect and are thought to help keep the tumor microenvironment immunosuppressive. This review also emphasizes how natural and synthetic modulators can prevent tumor growth by altering macrophage function or polarization. These innate immune cells are not only important in cancer but also play a crucial role in autoimmune diseases, allergic responses, and metabolic disorders. Learning about macrophage polarization will help scientists develop drugs that target TAMs, thereby helping tumors shrink.